2020
DOI: 10.3389/fonc.2020.00432
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Levels and Red Blood Cells Distribution Width Highlights Glioblastoma Patients Subgroup With Improved Median Overall Survival

Abstract: Glioblastoma multiforme (GBM) is known for its dismal prognosis, though its dependence on patients' readily available RBCs parameters is not fully established. In this work, 170 GBM patients, diagnosed and treated in Soroka University Medical Center (SUMC) over the last 12 years were retrospectively inspected for their survival dependency on pre-operative RBCs parameters. Besides KPS and tumor resection supplemented by oncological treatment, age under 70 (HR = 0.4, 95% CI 0.24-0.65, p = 0.00073), low hemoglobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Recently, studies have demonstrated that hematological markers may reflect the tumor microenvironment to some extent in GBM ( 10 , 17 , 19 , 20 ). Inflammation in the tumor microenvironment promotes angiogenesis, tumor invasion, and metastasis, while increasing tumor cell proliferation and enhancing their survival, and also destroying the body’s innate and adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies have demonstrated that hematological markers may reflect the tumor microenvironment to some extent in GBM ( 10 , 17 , 19 , 20 ). Inflammation in the tumor microenvironment promotes angiogenesis, tumor invasion, and metastasis, while increasing tumor cell proliferation and enhancing their survival, and also destroying the body’s innate and adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that a state of preoperative hypercoagulability is related to poor prognosis in patients with GBM ( 16 , 17 ). Other factors such as glucose (GLC) ( 18 , 19 ), hemoglobin (HBG) ( 20 , 21 ), the prognostic nutrition index (PNI) ( 14 , 22 , 23 ), lactate dehydrogenase (LDH) ( 24 , 25 ) and red blood cell distribution width (RDW) ( 20 , 26 ) have also been shown to have prognostic value in GBM. Fortunately, these hematological indicators can be obtained from convenient and inexpensive preoperative clinical routine tests.…”
Section: Introductionmentioning
confidence: 99%
“…In anemia condition, a fall in the level of haemoglobin (Hb) results into inefficient oxygen carrying capacity of the blood that eventually increases mortality in CVDs [9], [10]. Similar to a low haemoglobin condition, high hematocrit or Hb levels is also linked to CVDs [11], [12]. In case of hematocrit, body makes too many red blood cells that makes the blood thicker and ultimately lead to clots, heart attacks, and stroke [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to a low haemoglobin condition, high hematocrit or Hb levels is also linked to CVDs [11], [12]. In case of hematocrit, body makes too many red blood cells that makes the blood thicker and ultimately lead to clots, heart attacks, and stroke [11], [12]. Some of the recent studies have directly associated the role of anemia in the dilation of left ventricular leading to left ventricular systolic dysfunction (LVSD) [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that a state of preoperative hypercoagulability is related to poor prognosis in patients with GBM (16,17). Other factors such as glucose (GLC) (18,19), hemoglobin (HBG) (20,21), the prognostic nutrition index (PNI) (14,22,23), lactate dehydrogenase (LDH) (24,25) and red blood cell distribution width (RDW) (20,26) have also been shown to have prognostic value in GBM. Fortunately, these hematological indicators can be obtained from convenient and inexpensive preoperative clinical routine tests.…”
Section: Introductionmentioning
confidence: 99%